2019
DOI: 10.1074/jbc.ra119.009214
|View full text |Cite
|
Sign up to set email alerts
|

Structure–function studies of tetrahydroprotoberberine N-methyltransferase reveal the molecular basis of stereoselective substrate recognition

Abstract: Edited by Joseph M. Jez Benzylisoquinoline alkaloids (BIAs) are a structurally diverse class of plant-specialized metabolites that have been particularly well-studied in the order Ranunculales. The N-methyltransferases (NMTs) in BIA biosynthesis can be divided into three groups according to substrate specificity and amino acid sequence. Here, we report the first crystal structures of enzyme complexes from the tetrahydroprotoberberine NMT (TNMT) subclass, specifically for GfTNMT from the yellow horned poppy (Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In the available crystal structures, up to 13 direct or water-mediated hydrogen bonds appear to position the cosubstrate ( Figure 4 ). The implicated residues are almost perfectly conserved in all cloned BIA NMTs, with the exception of one non-conservative substitution (Gln to His) in PsRNMT ( Supplementary Figure 6 ) (Torres et al, 2016; Bennett et al, 2018; Lang et al, 2019). Comparison of the apoenzyme and binary complexes (e.g., TfPavNMT versus TfPavNMT + SAH) revealed only a minor hinge movement of domains relative to that seen in the OMTs.…”
Section: Molecular and Structural Determinants Of Functionmentioning
confidence: 89%
See 4 more Smart Citations
“…In the available crystal structures, up to 13 direct or water-mediated hydrogen bonds appear to position the cosubstrate ( Figure 4 ). The implicated residues are almost perfectly conserved in all cloned BIA NMTs, with the exception of one non-conservative substitution (Gln to His) in PsRNMT ( Supplementary Figure 6 ) (Torres et al, 2016; Bennett et al, 2018; Lang et al, 2019). Comparison of the apoenzyme and binary complexes (e.g., TfPavNMT versus TfPavNMT + SAH) revealed only a minor hinge movement of domains relative to that seen in the OMTs.…”
Section: Molecular and Structural Determinants Of Functionmentioning
confidence: 89%
“…An initial investigation was reported for T. flavum pavine NMT (PDB 5KOK) and, recently, for C. japonica coclaurine NMT (PDB 6GKV) (Torres et al, 2016; Bennett et al, 2018). A third report concerning the tetrahydroprotoberberine NMT from G. flavum was accepted for publication during the preparation of this manuscript (PDB 6P3O) (Lang et al, 2019). Taken together, these three studies cover much of the functional range reported to date for BIA NMTs and reveal many of the molecular determinants of function.…”
Section: Molecular and Structural Determinants Of Functionmentioning
confidence: 99%
See 3 more Smart Citations